2020
DOI: 10.1093/ckj/sfaa033
|View full text |Cite
|
Sign up to set email alerts
|

Acute interstitial nephritis due to sodium-glucose co-transporter 2 inhibitor empagliflozin

Abstract: Biopsy-proven acute interstitial nephritis (AIN) secondary to sodium-glucose co-transporter 2 (SGLT2) inhibitors has not been described previously. Here, we report on the management of a patient with severe acute kidney injury that developed 6 weeks after starting empagliflozin. The cause was confirmed as AIN on renal biopsy. Our patient recovered, without the need for dialysis, with discontinuation of empagliflozin and corticosteroid treatment. This novel clinical observation is likely to occur more frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The patient presented with fever, generalized erythema, and increased eosinophil levels, and a renal biopsy showed infiltration of eosinophils in the interstitium. There have been three previous reports of AIN induced by empagliflozin using the same SGLT-2 inhibitor, but none of them showed either fever or skin symptoms such as increased eosinophils in the peripheral blood or erythema (12)(13)(14). This is the first report of DRESS followed by AIN due to SGLT-2 inhibitors.…”
Section: Discussionmentioning
confidence: 75%
“…The patient presented with fever, generalized erythema, and increased eosinophil levels, and a renal biopsy showed infiltration of eosinophils in the interstitium. There have been three previous reports of AIN induced by empagliflozin using the same SGLT-2 inhibitor, but none of them showed either fever or skin symptoms such as increased eosinophils in the peripheral blood or erythema (12)(13)(14). This is the first report of DRESS followed by AIN due to SGLT-2 inhibitors.…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge, this case is the second report of biopsy-proven TIN caused by an SGLT2 inhibitor. The first case, reported by Ryan et al (15), showed histological findings of ATIN with lymphocytic infiltration in the interstitium under the background change of diabetic nephropathy. These findings were from a renal biopsy performed after 6 weeks of empagliflozin use in a patient who had had T2DM for 10 years (15).…”
Section: Discussionmentioning
confidence: 99%
“…The first case, reported by Ryan et al (15), showed histological findings of ATIN with lymphocytic infiltration in the interstitium under the background change of diabetic nephropathy. These findings were from a renal biopsy performed after 6 weeks of empagliflozin use in a patient who had had T2DM for 10 years (15). In our study, the findings of diabetic nephropathy were poor, and we also performed immunostaining for cell surface antigens and revealed that the infiltrated cells were positive for CD3 (expressed on T cells), CD45 (T cells), and CD68 (macrophages) and negative for CD22 (B cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its widespread use at present, there are only two case reports of ATIN associated with use of SGLT2is for standard indications. 12,13 Assuming that the PD-L1/SGLT2 colocalization on tumor cells is present in vivo in humans, one potential explanation for this may be that the interaction between PD-L1 and SGLT2 as observed by Ding and colleagues is unique to cancer cells. Indeed, human kidney biopsy specimens show low levels of basal PD-L1 expression in a normal proximal tubular epithelium.…”
mentioning
confidence: 99%